Effect of prophylactic treatment with levetiracetam on the incidence of postattenuation seizures in dogs undergoing surgical management of single congenital extrahepatic portosystemic shunts. Issue 2 (27th December 2018) - Mullins, Ronan A.; Sanchez Villamil, Carlos; de Rooster, Hilde; Kummeling, Anne; White, Robert N.; Thieman Mankin, Kelley M.; Tivers, Michael S.; Yool, Donald A.; Anderson, Davina M.; Pratschke, Kathryn M.; Gordo, Ines; Brissot, Herve; et al.
Abstract: Objective: To report the incidence of postattenuation seizures (PAS) in dogs that underwent single congenital extrahepatic portosystemic shunt (cEHPSS) attenuation and to compare incidence of PAS in dogs that either did or did not receive prophylactic treatment with levetiracetam (LEV). Study design: Multi‐institutional retrospective study. Population: Nine hundred forty dogs. Methods: Medical records were reviewed to identify dogs that underwent surgical attenuation of a single cEHPSS from January 2005 through July 2017 and developed PAS within 7 days postoperatively. Dogs were divided into 3 groups: no LEV (LEV−); LEV at ≥15 mg/kg every 8 hours for ≥24 hours preoperatively or a 60 mg/kg intravenous loading dose perioperatively, followed by ≥15 mg/kg every 8 hours postoperatively (LEV1); and LEV at <15 mg/kg every 8 hours, for <24 hours preoperatively, or continued at <15 mg/kg every 8 hours postoperatively (LEV2). Results: Seventy‐five (8.0%) dogs developed PAS. Incidence of PAS was 35 of 523 (6.7%), 21 of 188 (11.2%), and 19 of 228 (8.3%) in groups LEV‐, LEV1, and LEV2, respectively. This difference was not statistically significant ( P  = .14). No differences between groups of dogs that seized with respect to investigated variables were identified. Conclusion: The overall incidence of PAS was low (8%). Prophylactic treatment with LEV according to the protocols that were investigated in our study was not associated with a reduced incidence of PAS. Clinical significance: Prophylactic treatment with LEV does not afford protection against development of PAS. Surgically treated dogs should continue to be monitored closely during the first 7 days postoperatively for seizures.